The Influence Of Recruitment And Selection On Employee Performance At PT Permata Biru Jaya In Palembang City - Satria, Rian; Ermelia, Sri; Mario, Asma (Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the influence of recruitment and employee selection on employee performance at PT Permata Biru Jaya in Palembang. The main issue addressed in this research is the suboptimal recruitment and selection processes, which have negatively impacted employee performance. A quantitative approach was employed, with data collected through questionnaires distributed to the entire population of 52 employees using a census method. Data analysis included validity and reliability tests, classical assumption testing, and multiple linear regression analysis. The results indicate that both recruitment and selection variables have a significant effect on employee performance, both simultaneously and partially. These findings highlight the importance of implementing standardized recruitment and selection procedures to ensure the acquisition of qualified employees who meet organizational needs. This research provides theoretical contributions to the field of human resource management and practical implications for improving HR practices within the compan.